Quantifying habitat preference of bottom trawling gear. (8th December 2020) - Hintzen, N T; Aarts, G; Poos, J J; Van der Reijden, K J; Rijnsdorp, A D
Abstract: Continental shelves around the world are subject to intensive bottom trawling. Demersal fish assemblages inhabiting these shelves account for one-fourth of landed wild marine species. Increasing spatial claims for nature protection and wind farm energy suppresses, however, the area available to fisheries. In this marine spatial planning discussion, it is essential to understand what defines suitable fishing grounds for bottom trawlers. We developed a statistical methodology to study the habitat preference of a fishery, accounting for spatial correlation naturally present in fisheries data using high-resolution location data of fishing vessels and environmental variables. We focused on two types of beam trawls to target sole using mechanical or electrical stimulation. Although results indicated only subtle differences in habitat preference between the two gear types, a clear difference in spatial distribution of the two gears was predicted. We argue that this change is driven by both changes in habitat preference as well as a change in target species distribution. We discuss modelling of fisheries' habitat preference in light of marine spatial planning and as support in benthic impact assessments.